AN OVERVIEW OF ARTIFICIAL INTELLIGENCE ETHICS AND REGULATIONS - Muxtarova Maxliyo Usmonali qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation.This article provides an overview of key initiatives that propose ways to approach AI ethics, regulation and sustainability. The role of moral values in the activity of artificial intelligence, the need for standardization from a moral point of view, and the need to develop moral principles and rules are justified. In the work, a comparison of the norms of using artificial intelligence of foreign countries, as well as various corporations, is analyzed.At the end of this article, I also comment on keeping AI ethics “pragmatic” towards a concept I call a “Minimum Viable Ethics” or “Minimum Viable Regulation” for AI — this is to ensure that we keep a sustainable strong pace in our AI research and development.